Sekolah Bermain (TPI/TPA/TKA/TPQ) dalam Pendidikan Islam - Nurhadi Nurhadi (AS-SABIQUN, 2019)
The child is a symbiosis of the love of the husband and wife during the process of marriage. The purpose of getting married is to get offspring. The offspring of the marriage that arises from the surge of blessed love is the pious and pious child. Basically education plays in Islam from the time in the womb. After being born, both parents should joke and play a lot of positive but nuanced Islamic religions. Swinging the child on the swing while playing sholawatan and rhythm kasidah and nasyid or sya’ir-sya'ir wisdom of the poet about good children and doing good to parents. The custom of the community when leaving their children was swung in a swing while being adjusted by sya'ir pearl hikmah anak sholeh. In Islamic school playing has begun since in the womb, history records the story of Isya bint Maryam. In the history mentioned when containing is recommended to read the surah Maryam, Yusuf and Yasin, so that the child is born beautiful like Mary, Handsome pious like Yusuf and kind hearted like the heart of Al-Qur'an surah Yasin. Make a game that has Islamic religious nuances at home, such as audio, pictures, dolls and other Islamic toys. The atmosphere of the house where the children live is full of educational and impressive games so children feel comfortable at home. In the world of education it is known as the Al-Qur'an Education Park (TPI / TPA / TKA / TPQ). An institution or place to study the Qur'an and the teachings of Islam. During the Apostle saw TPI / TPA / TKA / TPQ were on the porch or terrace of the mosque. Learning patterns at TPI / TPA / TKA / TPQ with a period of one year, using the Al-Qur'an reading method, for example Iqra ', qira’ati and Yanbu'a.